Oxide-based solid electrolyte powder for use in lithium-ion secondary batteries, its manufacturing method, solid electrolyte layer, and lithium-ion secondary battery

By creating an oxide-based solid electrolyte powder with a highly fluorinated surface layer, the method addresses the limitations of uniform fluorine dispersion in existing technologies, enhancing lithium ion conductivity and improving battery performance.

JP7618959B2Active Publication Date: 2025-01-22AGC INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2019198755
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2019-10-31
Publication Date
2025-01-22
Estimated Expiration
2039-10-31

AI Technical Summary

Technical Problem

Existing methods for producing lithium ion conductive solid electrolytes using a solid phase reaction method result in uniform fluorine dispersion, leading to the formation of low ionic conductivity LiF within the electrolyte, limiting productivity and decreasing overall conductivity.

Method used

A method to produce an oxide-based solid electrolyte powder with a highly fluorinated surface layer, where the fluorine content on the outermost surface is 95% by mass or more and the total fluorine content is 10% by mass or less, ensuring a lithium ion conduction path and reducing grain boundary resistance.

Benefits of technology

The highly fluorinated surface layer enhances lithium ion conductivity and improves battery characteristics by stabilizing the particle surface, reducing hydrolysis resistance, and facilitating easier handling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007618959000001
    Figure 0007618959000001
Patent Text Reader

Abstract

To provide an oxide-based solid electrolyte powder for a lithium ion secondary battery having improved battery characteristics.SOLUTION: An oxide-based solid electrolyte powder used for a lithium ion secondary battery includes a particle having a fluorinated layer on the surface, the fluorine content on the outermost surface of the fluorinated layer is 95 mass% or more, and the fluorine content in the entire oxide-based solid electrolyte powder is 10 mass% or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an oxide-based solid electrolyte powder for use in a lithium ion secondary battery, a method for producing the same, a solid electrolyte layer, and a lithium ion secondary battery. [Background technology]

[0002] Lithium ion secondary batteries are widely used in portable electronic devices such as mobile phones and notebook computers. In recent years, there has been a demand for smaller and lighter lithium-ion secondary batteries for such portable electronic devices and vehicles, and further improvements in performance, such as discharge capacity per unit mass, cycle characteristics, rate characteristics, and battery stability, are desired.

[0003] Conventionally, liquid electrolytes have been used in lithium-ion secondary batteries, but all-solid-state lithium-ion secondary batteries that use solid electrolytes as the electrolyte have been attracting attention because of the potential for improved safety and high-speed charging and discharging.

[0004] For such lithium ion secondary batteries, methods for improving the lithium ion conductivity have been studied. For example, Patent Document 1 discloses a method for producing a lithium ion conductive solid electrolyte with improved lithium ion conductivity by mixing lithium niobate (LiNbO3) and a fluoride by a solid-state reaction method. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2013-157090 A Summary of the Invention [Problem to be solved by the invention]

[0006] In Patent Document 1, fluorine is introduced into a solid electrolyte by a solid-state reaction method in order to increase lithium ion conductivity. However, when fluorine is introduced by a solid-state reaction method, fluorine is uniformly dispersed in the solid electrolyte. Therefore, LiF with low ion conductivity is formed not only on the surface of the solid electrolyte but also inside the solid electrolyte, and there is a concern that the ion conductivity of the solid electrolyte itself will decrease. In addition, since the introduction of fluorine by the solid-state reaction method is performed by a mechanical milling method or the like, although it is simple, there is a limit to the amount of solid electrolyte that can be produced at one time, and there is also a problem of poor productivity.

[0007] Therefore, an object of the present invention is to provide an oxide-based solid electrolyte powder for a lithium ion secondary battery that improves battery characteristics. Specifically, an object of the present invention is to improve lithium ion conductivity by ensuring a conduction path for lithium ions on the surfaces of particles contained in the oxide-based solid electrolyte powder. [Means for solving the problem]

[0008] As a result of extensive investigations, the present inventors have found that the above-mentioned problems can be solved by highly fluorinating the surfaces of particles contained in an oxide-based solid electrolyte powder and setting the fluorine content in the entire powder to a specific range or less, and have completed the present invention.

[0009] That is, the present invention relates to the following [1] to [6]. [1] An oxide-based solid electrolyte powder for use in a lithium-ion secondary battery, The oxide-based solid electrolyte powder includes particles having a fluorinated layer on the surface, the fluorine content at the outermost surface of the fluorinated layer is 95% by mass or more; The fluorine content in the entire oxide-based solid electrolyte powder is 10 mass% or less. Oxide solid electrolyte powder. [2] The oxide-based solid electrolyte powder according to [1] above, wherein the particles have an average particle size of 0.1 to 100 μm. [3] The oxide-based solid electrolyte powder according to the above [1] or [2], wherein the fluorinated layer has a thickness of 1 to 50 nm. [4] A method for producing an oxide-based solid electrolyte powder including particles having a fluorinated layer on the surface thereof by contacting particles of an oxide-based solid electrolyte with a gas containing elemental fluorine, comprising the steps of: the fluorine content at the outermost surface of the fluorinated layer is 95% by mass or more; The fluorine content in the entire oxide-based solid electrolyte powder is 10 mass% or less. A method for producing an oxide-based solid electrolyte powder. [5] A solid electrolyte layer comprising the oxide-based solid electrolyte powder according to any one of the above [1] to [3]. [6] A lithium ion secondary battery comprising the solid electrolyte layer according to [5] above, a positive electrode, and a negative electrode. Effect of the Invention

[0010] According to the oxide-based solid electrolyte powder of the present invention, the surfaces of the particles contained in the powder are highly fluorinated, so that a conduction path for lithium ions can be secured on the particle surfaces, and the battery characteristics of a lithium ion secondary battery can be improved. In addition, it is believed that the high concentration of fluorination on the surfaces of particles contained in the oxide-based solid electrolyte powder stabilizes the particle surfaces and improves water repellency, which results in improved hydrolysis resistance and easier handling. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present invention will be described in detail below, but the present invention is not limited to the following embodiments and can be modified as desired without departing from the gist of the present invention. In addition, the symbol "to" indicating a numerical range is used to mean that the numerical values ​​before and after the symbol are included as the lower and upper limits.

[0012] <Oxide solid electrolyte powder> The oxide-based solid electrolyte powder according to this embodiment is used in lithium ion secondary batteries. The powder is characterized in that it contains particles having a fluorinated layer on the surface, the fluorine content of the outermost surface of the fluorinated layer is 95% by mass or more, and the fluorine content of the entire oxide-based solid electrolyte powder is 10% by mass or less. In the present invention, the "fluorine content at the outermost surface of the fluorinated layer" refers to the fluorine content at a depth of 2 nm from the surface of the fluorinated layer, excluding particle constituent components (components that constitute particles, described below). "Excluding particle constituent components" means excluding particle constituent components that diffuse or migrate from the particles to the fluorinated layer.

[0013] In the present invention, the surfaces of the particles contained in the oxide-based solid electrolyte powder are highly fluorinated, thereby reducing the resistance at the interface between the particles (hereinafter also referred to as grain boundary resistance), thereby ensuring the conduction path of lithium ions on the surfaces of the particles and improving the lithium ion conductivity.

[0014] The reason why the grain boundary resistance can be reduced by fluorinating the surfaces of particles contained in the oxide-based solid electrolyte powder to a high concentration is not clear, but is presumed to be as follows. That is, the particle interface formed between the surfaces of the particles contained in the solid electrolyte powder is selectively and highly fluorinated with fluorine gas, hydrogen fluoride gas, or the like, thereby lowering the melting point of the grain boundary portion. Therefore, when the solid electrolyte powder is heat-treated to form a sheet-shaped solid electrolyte layer, the surfaces of the particles contained in the solid electrolyte powder are easily dissolved, improving the adhesion between the particles. As a result, it is presumed that the grain boundary resistance is reduced and the lithium ion conductivity is improved. Alternatively, it is possible that the particle surface is stabilized by fluorination, while the presence of fluorine, which has a high electronegativity, polarizes the particle surface, and the interaction with lithium ions reduces the grain boundary resistance at the electrolyte interface, resulting in the formation of an excellent lithium ion conduction path.

[0015] As for the improvement of hydrolysis resistance, it is presumed that the surfaces of the particles contained in the oxide-based solid electrolyte powder are fluorinated at a high concentration, thereby stabilizing the particle surfaces, thereby improving hydrolysis resistance.

[0016] The oxide-based solid electrolyte powder according to this embodiment contains oxide-based solid electrolyte particles having a fluorinated surface layer. The particles are not particularly limited as long as they are oxide-based, and those containing oxygen (O) and having lithium ion conductivity can be suitably used. For example, perovskite-type oxides containing lithium, garnet-type oxides containing lithium, lithium phosphate (Li3PO4), lithium niobate (LiNbO3), LAGP (LiPO4) with a NASICON structure, and the like can be used. 1+x Al x Ge 2-x (PO4)3(0≦x≦1)), NASICON structure LATP(Li 1+x Al x Ti 2-x (PO4)3(0≦x≦1)), NASICON structure LZP(Li 1+4x Zr 2―x(PO4)3 (0≦x≦0.4, some of the metal elements in LZP may be replaced with other metal elements, or other metal elements may be doped. Examples of other metal elements include Na, Sr, Ca, Mg, La, Y, Sc, Ce, In, Al, Ge, Ti, and V.) These may be used alone or in combination.

[0017] The perovskite oxide containing lithium is an oxide having a perovskite crystal structure and represented by ABO3, and it is preferable that the A site contains at least one element selected from the group consisting of La, Sr, Ba, Na, Ca, and Nd, and Li, and the B site contains at least one element selected from the group consisting of Ti, Ta, Cr, Fe, Co, Ga, and Nb. Specifically, the perovskite oxide is lithium lanthanum titanate Li 3x La 2 / 3-x TiO3 (0≦x≦1 / 6, also known as LLTO), lithium lanthanum niobate (Li x La (1-x) / 3 NbO3) (0≦x≦1), etc. In addition, some of the elements constituting lithium lanthanum titanate may be replaced with other elements, or other elements may be doped. Examples of other elements include Na, K, Rb, Ag, Tl, Mg, Sr, Ca, Ba, Nb, Ta, W, Ru, Cr, Mn, Fe, Co, Al, Ga, Si, Ge, Zr, Hf, Pr, Nd, Sm, Gd, Dy, Y, Eu, Tb, etc., and specifically, La (2 / 3)-x Sr x Li x TiO3, Li x La 2 / 3 Ti 1-x Al x Examples include O3.

[0018] Garnet-type oxides include, for example, Li7La3Zr2O 12 , Li5La3Nb2O 12 , Li5La3Ta2O 12 , and Li6La2BaTa2O 12 etc.

[0019] The oxide-based solid electrolyte of the present invention can be applied not only to crystalline materials but also to amorphous materials, which may be composited with Li4SiO4, Li3PO4, Li3BO3, SiO2, B2O3, etc.

[0020] The shape of the particles contained in the oxide-based solid electrolyte powder according to this embodiment may be a primary particle, a secondary particle formed by agglomeration of primary particles, or a combination of primary particles and secondary particles. When the particle shape is a primary particle, the surface of the primary particle may be fluorinated, and when the particle shape is a secondary particle, the surface of the secondary particle formed by agglomeration of primary particles may be fluorinated. From the viewpoint of the effects of the present invention, it is preferable that the oxide-based solid electrolyte powder according to this embodiment contains secondary particles, and the surface of the secondary particles is fluorinated. In this manner, the surfaces of the particles contained in the oxide-based solid electrolyte powder are covered with a fluorinated layer, thereby improving the lithium ion conductivity by forming a conduction path for the lithium ions, and improving the battery characteristics of the lithium ion secondary battery.

[0021] In the oxide-based solid electrolyte powder according to this embodiment, the fluorinated layer has a fluorine content of 95% by mass or more at the outermost surface. When the fluorine content of the outermost surface is 95% by mass or more, the particle surface is fluorinated at a high concentration, and lithium ion conductivity is improved. The fluorine content of the outermost surface is more preferably 97% by mass or more. The fluorine content at the outermost surface of the fluorinated layer is measured by the following method: the fluorine content, excluding particle constituents, at a depth of 2 nm from the surface of the fluorinated layer is measured by element mapping using a transmission electron microscope (TEM) or by depth element profile analysis from the particle surface to the inside of the grain using ESCA (X-ray photoelectron spectroscopy).

[0022] In addition, when the fluorinated layer is formed by hydrogen fluoride gas (HF gas) described later, a small amount of hydrogen is present on the outermost surface of the fluorinated layer. In this case, the hydrogen content on the outermost surface of the fluorinated layer is preferably 0.1 to 5 mass%, more preferably 0.1 to 3 mass%. By being in the above range, the influence of the small amount of hydrogen on the outermost surface of the fluorinated layer can be minimized. The hydrogen content at the outermost surface of the fluorinated layer can be measured in the same manner as the fluorine content described above.

[0023] The fluorine content in the entire oxide-based solid electrolyte powder according to this embodiment is 10% by mass or less. By being 10% by mass or less, the fluorine content present inside the particles is reduced, and the decrease in lithium ion conductivity caused by the deterioration of crystallinity and the excess of low ion conductive components can be reduced. In addition, the decrease in conductivity due to insulating LiF can also be suppressed. The fluorine content in the entire oxide-based solid electrolyte powder is preferably 9% by mass or less, more preferably 8% by mass or less. In addition, the total fluorine content is preferably 0.1% by mass or more in order to form a fluorinated layer on the surface of the particles, more preferably 1% by mass or more, and even more preferably 2% by mass or more. The fluorine content can be determined from the results of elemental analysis by a combustion method as described in the Examples below.

[0024] The thickness of the fluorinated layer is preferably 1 nm or more, more preferably 1.25 nm or more, and even more preferably 1.5 nm or more, from the viewpoint of obtaining the effects of the present invention more effectively. Also, the thickness of the fluorinated layer is preferably 50 nm or less, more preferably 20 nm or less, and even more preferably 10 nm or less, from the viewpoint of suppressing a decrease in electrical conductivity. In particular, when the shape of the particles contained in the oxide-based solid electrolyte powder includes secondary particles, the thickness of the fluorinated layer in the secondary particles is preferably 1 nm or more, more preferably 1.25 nm or more, and even more preferably 1.5 nm or more, and the thickness of the fluorinated layer is preferably 50 nm or less, more preferably 20 nm or less, and even more preferably 10 nm or less. The thickness of the fluorinated layer can be determined by analysis such as X-ray photoelectron spectroscopy or element mapping from the particle cross section.

[0025] The average particle size of the particles having a fluorinated layer is preferably 0.1 μm or more, more preferably 0.5 μm or more, and even more preferably 1 μm or more, from the viewpoint of stable formation, and is preferably 100 μm or less, more preferably 50 μm or less, and even more preferably 20 μm or less, from the viewpoint of ease of lithium ion mobility. The average particle size of particles having a fluorinated layer on the surface includes the thickness of the fluorinated layer and is determined by a particle size distribution measuring device. Usually, the D50 average particle size (median size: particle size at which the cumulative frequency is 50%) can be used. Specifically, oxide-based solid electrolyte powder is thoroughly dispersed in water by ultrasonic treatment, and the particles are measured using a laser diffraction / scattering particle size distribution analyzer. A frequency distribution and a cumulative volume distribution curve are obtained to obtain a volume-based particle size distribution, and the particle size at the 50% point on the cumulative volume distribution curve is defined as the D50 average particle size.

[0026] <Method of manufacturing oxide-based solid electrolyte powder> The method for producing an oxide-based solid electrolyte powder according to the present embodiment is characterized in that the oxide-based solid electrolyte powder having a fluorinated layer according to the above embodiment is produced by contacting particles of an oxide-based solid electrolyte with a gas containing elemental fluorine. That is, by contacting particles of an oxide-based solid electrolyte before fluorination with a gas capable of fluorination, a fluorinated layer can be formed on the particle surface, and the oxide-based solid electrolyte powder according to the above embodiment can be produced.

[0027] The fluorinable gas is a gas containing fluorine element, and examples thereof include fluorine gas (F2 gas), hydrogen fluoride gas (HF gas), BF3 gas, NF3 gas, PF5 gas, SiF4 gas, and SF6 gas. These fluorine element-containing gases may be used alone or in combination with an inert gas such as nitrogen gas or argon gas. The fluorinated layer in the present invention may contain these gas components.

[0028] Among these, fluorine gas (F2 gas) or hydrogen fluoride gas (HF gas) is preferred because it does not contain other elements in the sense that it reacts only with fluorine. When a fluorinated layer is formed by contacting the particles with F2 gas or HF gas, it can be determined that the fluorinated layer is formed by contact with such gas, since only fluorine atoms or hydrogen atoms are contained in the solid electrolyte. In particular, fluorine gas is preferred from the viewpoint of being able to increase the fluorine content at the outermost surface of the fluorinated layer.

[0029] When a mixed gas is used, the concentration of the gas containing elemental fluorine is preferably 0.01% by volume or more, more preferably 0.1% by volume or more, based on the total mixed gas, from the viewpoints of ease of reaction control and economy. The concentration of the gas containing elemental fluorine is preferably 50% by volume or less, more preferably 35% by volume or less, and even more preferably 20% by volume or less.

[0030] The time for contacting the oxide-based solid electrolyte particles with the gas containing elemental fluorine is preferably 10 seconds or more, more preferably 1 minute or more, and is preferably 240 minutes or less, more preferably 150 minutes or less. By setting the time within this range, a fluorinated layer with a controlled concentration can be formed on the surface of the particles with good accuracy.

[0031] The temperature at which the oxide-based solid electrolyte particles are brought into contact with the gas containing elemental fluorine is preferably controlled within a range of 10 to 150° C. When it is desired to increase the fluorine concentration on the particle surface, the temperature can be raised to increase the reactivity between the particle surface and fluorine, thereby forming a layer containing the desired fluorine at a high concentration. This allows the fluorinated layer to be formed reliably and efficiently.

[0032] The contact with the gas containing elemental fluorine may be carried out under pressure, and the pressure is preferably 0.6 MPa (gauge pressure) or less, more preferably 0.3 MPa or less, from the viewpoints of enhancing safety and suppressing excessive fluorination.

[0033] The contact with the gas containing elemental fluorine is preferably carried out in a flow manner or a batch manner. In the case of the flow-through type, a method is preferred in which the particles are placed in a reaction vessel in a stationary state, and a gas containing fluorine at a predetermined concentration is continuously supplied into an open reaction vessel to bring the particles into contact with the gas containing fluorine. In the case of the batch type, a method is preferred in which the particles are placed in a sealed reaction vessel in an atmosphere of a gas containing elemental fluorine at a prescribed concentration and the particles are brought into contact with the gas containing elemental fluorine.

[0034] When the flow-type reaction is carried out, from the viewpoint of uniformly contacting the particles with a gas containing elemental fluorine, a reaction vessel equipped with a fluidized bed in which the particles are placed and fluidized, or a kiln such as a tubular furnace, can also be used. The use of a fluidized bed is particularly preferred, since it can shorten the fluorination treatment time and suppress excessive fluorination, thereby realizing more uniform fluorination. When the batch method is used, the particles may be stirred and mixed in order to bring the gas containing elemental fluorine into contact with the particles uniformly.

[0035] <Solid electrolyte layer> The solid electrolyte layer according to the present embodiment contains the oxide-based solid electrolyte powder and is used in a lithium-ion secondary battery. In addition, it may contain a binder as necessary. The content of the solid electrolyte powder in the solid electrolyte layer is not particularly limited and may be appropriately determined depending on the performance of the target battery. For example, the content of the solid electrolyte powder is preferably 80% by mass or more, more preferably 90% by mass or more, based on 100% by mass of the entire solid electrolyte layer.

[0036] Examples of binders that can be contained in the solid electrolyte layer include butadiene rubber (BR), acrylate butadiene rubber (ABR), styrene butadiene rubber (SBR), polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE), etc. The content of the binder in the solid electrolyte layer may be the same as that of a conventional binder.

[0037] The thickness of the solid electrolyte layer is not particularly limited and may be appropriately determined according to the performance of the intended battery. For example, it is preferably 10 μm or more, more preferably 15 μm or more. By making the thickness of the solid electrolyte layer 10 μm or more, the mechanical strength is increased, and it is possible to obtain a solid electrolyte layer that is resistant to stresses such as vibration and bending and has high reliability. The thickness of the solid electrolyte layer is preferably 200 μm or less, and more preferably 100 μm or less. By making the thickness of the solid electrolyte layer as thin as 200 μm or less, it is possible to increase the ionic conductivity between the positive and negative electrodes and also to increase the energy density of the battery.

[0038] The method for forming the solid electrolyte layer is not particularly limited. For example, the components constituting the solid electrolyte layer described above are dispersed or dissolved in a solvent to form a slurry, which is then coated in a layer (sheet), dried, and optionally pressed to form the solid electrolyte layer. If necessary, a binder removal treatment may be performed by applying heat. The thickness of the solid electrolyte layer can be easily adjusted by adjusting the coating amount of the slurry, etc. Instead of the wet molding as described above, the solid electrolyte layer may be formed by dry press molding of a solid electrolyte powder or the like on the surface of the object (positive electrode, negative electrode, etc.) on which the solid electrolyte layer is to be formed. Alternatively, the solid electrolyte layer may be formed on another substrate, which is then transferred to the surface of the object on which the solid electrolyte layer is to be formed. From the viewpoint of being able to industrially and stably form a strong solid electrolyte layer on the surface of the object on which the solid electrolyte layer is to be formed, it is preferable to form the solid electrolyte layer on the surface of the object by wet molding using a solvent.

[0039] <Lithium-ion secondary battery> The lithium ion secondary battery according to this embodiment includes the above-mentioned solid electrolyte layer, a positive electrode, and a negative electrode. The positive electrode and the negative electrode may be conventionally known. Specific examples are shown below, but are not limited thereto.

[0040] (positive electrode) The positive electrode contains at least a positive electrode current collector and a positive electrode active material.

[0041] The positive electrode current collector may be any conductive plate material, for example, a thin metal plate (metal foil) of aluminum or an alloy thereof, stainless steel, etc. These are preferred because they have excellent electrolyte resistance and oxidation resistance.

[0042] The positive electrode active material is a material that absorbs and releases lithium ions, removes and inserts lithium ions (intercalates), or has a counter anion (e.g., PF6 - As long as the doping and dedoping of Li(II) can be carried out reversibly, the positive electrode active material is not particularly limited, and a known positive electrode active material can be used. Examples of the positive electrode active material include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganate (LiMnO2), lithium nickel manganate, Li(Ni x Co y Mn z M a )O2 (x+y+z+a=1, 0≦x≦1, 0≦y≦1, 0≦z≦1, 0≦a≦1, and M is at least one selected from Al, Mg, Nb, Ti, Cu, Zn, and Cr), Li a M b (PO4) c (1≦a≦4, 1≦b≦2, 1≦c≦3, and M is at least one selected from Fe, V, Co, Mn, Ni, and VO).

[0043] The positive electrode may contain a binder that binds the positive electrode active materials together and also binds the positive electrode active material to the positive electrode current collector. Any binder known in the art can be used. The positive electrode may also contain a known conductive assistant for positive electrodes, examples of which include carbon-based materials such as graphite and carbon black, metals such as copper, nickel, stainless steel, and iron, and conductive oxides such as indium tin oxide (ITO).

[0044] (Negative electrode) The negative electrode contains at least a negative electrode current collector and a negative electrode active material.

[0045] The negative electrode current collector may be any conductive plate material, for example, a thin metal plate (metal foil) of copper, aluminum, etc. These are preferred because they have excellent electrolyte resistance and oxidation resistance.

[0046] The negative electrode active material is not particularly limited, and may be any material capable of inserting and extracting lithium ions, such as lithium metal, carbon-based materials, silicon, silicon alloys, and tin. The negative electrode active material is capable of absorbing and releasing lithium ions, desorbing and inserting lithium ions (intercalation), or providing a counter anion of the lithium ion (e.g., PF6 - As long as the doping and dedoping of lithium can be carried out reversibly, the negative electrode active material is not particularly limited, and a known negative electrode active material can be used. Examples of the negative electrode active material include carbon materials such as graphite, hard carbon, and soft carbon, metals that can form alloys with lithium such as aluminum, silicon, and tin, amorphous oxides such as silicon oxide and tin oxide, and lithium titanate (Li4Ti5O 12 ) etc.

[0047] In addition, the negative electrode may have a binder that binds the negative electrode active materials together and also binds the negative electrode active material to the negative electrode current collector. Any binder known in the art can be used. The negative electrode may contain a known conductive assistant for negative electrodes, and the same conductive assistant for positive electrodes as described above can be used.

[0048] The components constituting the lithium ion secondary battery, such as the solid electrolyte layer, the positive electrode, and the negative electrode, are housed in a battery exterior body. The material of the battery exterior body may be a conventionally known material, and specific examples thereof include nickel-plated iron, stainless steel, aluminum or alloys thereof, nickel, titanium, resin materials, and film materials.

[0049] The shape of the lithium ion secondary battery may be a coin type, a sheet type (film type), a folded type, a wound type with a bottom, a cylindrical type, a button type, etc., and may be appropriately selected depending on the application.

[0050] The lithium ion secondary battery according to this embodiment can achieve good lithium ion conductivity. EXAMPLES

[0051] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these.

[0052] [Example 1 (Example) Fluorinated oxide-based solid electrolyte powder] (Li 0.35 La 0.55 Synthesis of TiO3 powder) 3.87g of lithium carbonate (Li2CO3) and 0.27g of lanthanum acetate (La(CH3COO)3·1.5H2O) were dissolved in 23.88g of water with stirring, and 11.98g of titanium lactate aqueous solution (Matsumoto Fine Chemical Co., Ltd., Orgatics TC-315, Ti content 8.3%) was slowly added. The resulting aqueous dispersion was dried at 80°C for 24 hours and then crushed using an agate mortar. It was then placed in an alumina container and heat-treated at 700°C for 4 hours, and passed through a 75μm mesh to synthesize powder. Measurement of the resulting powder using an X-ray diffractometer (Rigaku, Smart Lab) revealed that Li 0.35 La 0.55 The formation of TiO3 was confirmed. The Li synthesized above was placed in a 0.3 L Hastelloy reactor. 0.35 La 0.55 Put 3g of TiO3 powder into the flask, and heat the Li gas at 2.5KPa and 140℃ for 2 hours using N2 gas containing 20% ​​by volume of F2 gas. 0.35 La 0.55 By fluorinating the TiO3 powder, Li with a fluorinated layer on the particle surface was obtained. 0.35 La 0.55 TiO3 powder was obtained. (Fluorine content on the outermost surface) ESCA analysis (X-ray photoelectron spectroscopy) was performed using an ESCA5500 (manufactured by ULVAC-PHI, Inc.), and the fluorine content in the outermost surface of the fluorinated layer was found to be 100% by mass. (Fluorine content in powder) The fluorine content was quantitatively analyzed using an automatic sample combustion device (Mitsubishi Chemical Analytech (Dia Instruments), AQF-100) and ion chromatography (Dionex, DX120). 0.35 La 0.55 The fluorine content in the entire TiO3 powder was 9 mass%. (Average particle size) The average particle size of the powder was measured using a laser diffraction / scattering type particle size distribution measuring device (manufactured by Nikkiso Co., Ltd., product name MT-3300EX) and was found to be 3 μm.

[0053] [Example 2 (Comparative Example) Fluorine-Untreated Oxide-Based Solid Electrolyte Powder] Unfluorinated Li 0.35 La 0.55 TiO3 powder was used. The average particle size of the powder was measured using a laser diffraction / scattering type particle size distribution measuring device (manufactured by Nikkiso Co., Ltd., product name MT-3300EX) and found to be 3 μm.

[0054] <Measurement of lithium ion conductivity> For the oxide-based solid electrolyte powders of Examples 1 and 2, the lithium ion conductivity was measured by the AC impedance method. The lithium ion conductivity was measured using a temperature variable high frequency impedance measuring device manufactured by Toyo Corporation. The measurement was carried out by depositing Au on the oxide solid electrolyte sample described below, pressing a SUS electrode against it from the outside, and performing the measurement under the conditions of an applied voltage of 20 mV, a measurement temperature of 25°C, and a measurement frequency range of 100 MHz to 20 Hz. The Li ion migration resistance was obtained by analyzing the Cole-Cole plot obtained from the AC impedance measurement, and the Li ion conductivity was calculated from the area and thickness of the pellet sample used for the measurement. Here, as the sample for measuring lithium ion conductivity, a pellet-shaped oxide-based solid electrolyte sample obtained by pressing the oxide-based solid electrolyte powders of Examples 1 and 2 at 30 kN for 2 minutes using a pressing device was used. The results are shown in Table 1. Each measurement value is the average of two measurements.

[0055] [Table 1]

[0056] From the above results, it was possible to increase the lithium ion conductivity in Example 1 compared to the oxide-based solid electrolyte powder not having a fluorinated layer in Example 2. It is presumed that this evaluation result is due to the fact that the grain boundary resistance was reduced by carrying out the fluorination treatment on the particle surfaces.

Claims

1. An oxide-based solid electrolyte powder for use in a lithium-ion secondary battery, The oxide-based solid electrolyte powder includes particles having a fluorinated layer on the surface, the fluorine content at the outermost surface of the fluorinated layer is 95% by mass or more, The fluorine content in the entire oxide-based solid electrolyte powder is 10 mass% or less, The average particle size of the particles is 0.5 to 100 μm. Oxide solid electrolyte powder.

2. 2. The oxide-based solid electrolyte powder according to claim 1, wherein the fluorinated layer has a thickness of 1 to 50 nm.

3. A method for producing an oxide-based solid electrolyte powder including particles having a fluorinated layer on the surface thereof by contacting particles of an oxide-based solid electrolyte with a gas containing elemental fluorine, comprising the steps of: The oxide-based solid electrolyte powder is used in a lithium-ion secondary battery, the fluorine content at the outermost surface of the fluorinated layer is 95% by mass or more, The fluorine content in the entire oxide-based solid electrolyte powder is 10 mass% or less, The particles have an average particle size of 0.5 to 100 μm; The gas containing elemental fluorine is F 2 Gas, HF gas, BF 3 Gas, NF 3 Gas, PF 5 Gas, SiF 4 Gas and SF 6 At least one selected from the group consisting of gases, A method for producing an oxide-based solid electrolyte powder.

4. A solid electrolyte layer comprising the oxide-based solid electrolyte powder according to claim 1 or 2.

5. A lithium ion secondary battery comprising the solid electrolyte layer according to claim 4, a positive electrode, and a negative electrode.

Citation Information

Patent Citations

  • Zirconia ceramic and production thereof

    JP1988303858A

  • Lithium ion conductive solid electrolyte

    JP2013157090A

  • Fluorine-doped oxide-based solid electrolyte

    JP2014523626A